Resolution of electric field distribution and conductivity in a non-uniform electric field: A teaching proposal - Erol, Mustafa; Çolak, İldahan Özdeyiş (Momentum: Physics Education Journal, 2021)
This work offers an alternative teaching proposal for the instruction of challenging concepts of electric field distribution and specific conductivity in a non-uniform electric field. Specifically, electric field lines are initially plotted and later on the relation between the electric potential difference and electric field strength is validated. Additionally, on a selected electric field line, electric field strength versus path length and also conductivity versus path length are plotted to comprehend and teach exceedingly difficult concepts of uniform and non-uniform electric fields. In order to accomplish those tasks, a basic conducting sheet, that is simply a wet cardboard, is designed as a part of the apparatus together with a dc power supply, a multi meter and connecting cables. The established method is interesting in the sense that designed the conducting wet cardboard is novel, very practical, beneficial and minimal costing, hence the approach offers physics educators fresh teaching routes and opportunities to clarify the puzzling concepts of electrical field and conductivity.